Photobiont Diversity in Lichen Symbioses From Extreme Environments - De Carolis, Roberto; Cometto, Agnese; Moya, Patricia; Barreno, Eva; Grube, Martin; Tretiach, Mauro; Leavitt, Steven D.; Muggia, Lucia (Frontiers in Microbiology, 2022)
Fungal-algae relationships both across evolutionary and ecological scales are finely modulated by the presence of the symbionts in the environments and by the degree of selectivity and specificity that either symbiont develop reciprocally. In lichens the green algal genus Trebouxia Puymaly is one of the most frequently recovered chlorobiont, for which species level lineages have been recognized on the base of their morphological and phylogenetic diversity, while their ecological preferences and distribution are still partially unknown. We selected two cosmopolitan species of lichen-forming fungi as reference models, i.e., Rhizoplaca melanophthalma and Tephromela atra, to investigate the diversity of their associated Trebouxia spp. in rather remote mountain areas, at high elevation across their distributional range worldwide. The greatest diversity of Trebouxia species level lineage was recovered in the altitudinal range 1000-2500 m a.s.l. A total of ten Trebouxia species-level lineages were found to associate with either mycobiont, for which new photobionts are reported. One new Trebouxia species level lineage was identified and is here provisionally named Trebouxia ‘A52’. Analyses of cell morphology and ultrastructure were performed on axenically isolated strains to fully characterized the new Trebouxia ‘A52’ and three other previously recognized lineages, i.e. Trebouxia ‘A02’, T. vagua ‘A04’ and T. vagua ‘A10’, which were successfully isolated in culture during this study. The species-level diversity of Trebouxia associating with the two lichen-forming fungi in extreme habitats help elucidate the evolutionary pathways that this lichen photobiont genus traversed to occupy varied climatic and vegetative regimes.